Biscuit Wants to Play - Capucilli, Alyssa; Schories, Pat (New York, 2001)
The puppy Biscuit makes friends with two kittens.
Keywords: Fiction; Animals; Fiction; Play; Dogs; Cats; Fiction; Fiction; Infancy